Challenges And Importance Of Teaching Balance Exercises To Young Artistic Gymnasts - Tuychiyeva Dildora Turgunovna (Euro Asian Journal Publishing, 2024)
Present article is devoted to the how to use balance exercises to young artistic gymnastics. The main point of teaching methods of them and also specific balance exercises in order to improve their skills on it.
Keywords: balance; body alignment; center of gravity; proprioception and body awareness